Brief interventions for adolescent alcohol and substance abuse - Monti, Peter M.; Colby, Suzanne M.; Tevyaw, Tracy O'Leary (The Guilford Press, 2018)
Bringing together leading experts, this book demonstrates the unique value of brief motivational interventions for addressing adolescent alcohol and other substance use in a range of clinical contexts. It presents cutting-edge knowledge on the etiology and developmental context of adolescent addictive behaviors and reviews exemplary treatment approaches.